Computational Scheme for Geosynchronous Satellite Orbit due to Gravitation of the Earth - Harijono Djojodiharjo; Yus Kadarusman (Institute for Research and Community Services (LPPM) ITB, 1982)
By analyzing the influence of the earth's gravitational anomaly on the orbit of a satellite around the earth, a computational scheme for geosynchronous satellite orbit with small inclination is developed. The governing equations of motion, which consist of three equations and have been simplified to take into account geosynchronous conditions and small displacements, are solved by numerical technique. In particular the radius of geosynchronous orbit is obtained by solving the first governing equation by Regula-Falsi method. Stationary points are obtained by indirect method, i.e. by first finding the longitude positions with zero longitudinal accelerations. The trajectory of the subsatellite point is obtained by solving the governing equations for small displacement by Runge-Kutta method. Comparison of computational result with Blitzer's and Flury's using IAU 1968 and GEM-8 data, leads confidence to the present scheme.